New perspectives on cohesion and coherence: (Language Science Press., 2017)
Contents: Cohesion and coherence in multilingual contexts; Discourse connectives: From historical origin to present-day development; Possibilities of text coherence analysis in the Prague Dependency Treebank; Applying computer-assisted coreferential analysis to a study of terminological variation in multilingual parallel corpora; Testing target text fluency: A machine learning approach to detecting syntactic translationese in English-Russian translation; Cohesion and translation variation: Corpus-based analysis of translation varieties; Examining lexical coherence in a multilingual setting.